Condition monitoring of zinc oxide surge arresters - Novizon, Novizon (InTech, 2011)
Over voltages in power system may occur due to lightning, fault or switching operation. These overvoltages could reach dangerous amplitudes for power system apparatus. To protect the system electrical equipment and to guarantee an economic and reliable operation, surge arresters are applied in almost all types of electrical power network. Gapless zinc oxide (ZnO) surge arresters are widely used. The surge arresters are usually connected between the phase and ground terminals. They limit the voltage level in equipments such as transformers below the withstand voltage level.